2020
DOI: 10.1186/s41205-020-00071-8
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial vasculature 3D printing: review of techniques and manufacturing processes to inform clinical practice

Abstract: Background: In recent years, three-dimensional (3D) printing has been increasingly applied to the intracranial vasculature for patient-specific surgical planning, training, education, and research. Unfortunately, though, much of the prior literature regarding 3D printing has focused on the end-product and not the process. In addition, for 3D printing/manufacturing to occur on a large scale, challenges and bottlenecks specific to each modeled anatomy must be overcome. Main body: In this review article, limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The process of creating the phantom also showed that 3D models should be printed as simply as possible, meaning that small unnecessary components/ artery branches should be removed before printing, because of the risk that they will break or rupture the silicone. This was also found in the study from Cogswell et al 23 The Ecoflex 00e35 silicone is very elastic, which is important when it has to be removed from the 3D printed model. The silicone layer that must cover the 3D model also has to be thick enough, for the 3D model not to penetrate.…”
Section: Discussionsupporting
confidence: 66%
“…The process of creating the phantom also showed that 3D models should be printed as simply as possible, meaning that small unnecessary components/ artery branches should be removed before printing, because of the risk that they will break or rupture the silicone. This was also found in the study from Cogswell et al 23 The Ecoflex 00e35 silicone is very elastic, which is important when it has to be removed from the 3D printed model. The silicone layer that must cover the 3D model also has to be thick enough, for the 3D model not to penetrate.…”
Section: Discussionsupporting
confidence: 66%
“…Intracranial aneurysms, vascular malformations, and complicated or difficult to locate vessels associated with brain tumors are just some of the pathologies that affect neurosurgical patients. Three-dimensional printing made it possible not only to create individual vascular models for each patient ( Figure 9 A,B) but also made it possible to prepare for surgery through training models for surgeons more accurately and to better explore the hemodynamics of these phenomena through scientific studies [ 99 ]. Currently, models are made with the greatest attention to detail so that the material fully reflects not only the shape of anatomical structures but also the tissues of which individual structures are made.…”
Section: Discipline Specific Applicationsmentioning
confidence: 99%
“…The majority of the methods proposed for the fabrication of vascular phantoms in neurosurgery and radioneurosurgery mainly rely on sacrificial templating for the realization of vascular networks in silicone-based materials or on the direct fabrication of solid models representing the vessels. [29][30][31][32][33][34] Although the realization of complex vascular networks is critical for strategies based on the use of soluble 3D templates, a higher level of anatomical details and topological complexity is available for the direct manufacturing of vascular solid models. However, the lack of an internal channelization in these systems does not allow implementing functional and physiological features related to the circulation of fluids into the phantoms.…”
Section: D Vascular Phantoms 223mentioning
confidence: 99%
“…13,[19][20][21][22] The most representative examples are mainly related to surgical aid applications (e.g., aneurysm clipping 20,23 ) as well as to diagnosis, 24,25 blood circulation analysis, 26,27 and patients' information purposes. 12 The manufacturing strategies explored included material extrusion of thermoplastic polymers (e.g., fused filament fabrication [FFF] 20,28 ), VAT photopolymerization, 29,30 PolyJet printing, 31,32 and sacrificial approaches combining FFF of acrylonitrile butadiene styrene (ABS) templates and casting of silicone-based materials. 33,34 In the SRS domain, a 3D morphofunctional phantom embedding the vascular structure of a patient-specific AVM would be of great importance.…”
Section: Introductionmentioning
confidence: 99%